The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1600-0420.2007.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical and systemic absorption in delivery of dexamethasone to the anterior and posterior segments of the eye

Abstract: ABSTRACT.Purpose: This study aimed to: (1) determine the relative efficiencies of topical and systemic absorption of drugs delivered by eyedrops to the anterior and posterior segments of the eye; (2) establish whether dexamethasone-cyclodextrin eyedrops deliver significant levels of drug to the retina and vitreous in the rabbit eye, and (3) compare systemic absorption following topical application to the eye versus intranasal or intravenous delivery. Methods: In order to distinguish between topical and systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 20 publications
3
52
0
1
Order By: Relevance
“…18 For diseases requiring long-term drug administration such as those of the retina and vitreous body, a dexamethasone/cyclodextrin mixture applied to the ocular surface increased retinal penetration two-fold relative to systemic administration. 19 In situ gels are a novel type of ophthalmic drug delivery system with a longer retention time than that of existing approaches, and they reduce administration frequency and improve bioavailability. In vivo studies have shown that a temperature-sensitive chitosan hydrogel administered as ocular drops had high penetration and sustained release over 12 h while reducing intraocular pressure.…”
Section: Introductionmentioning
confidence: 99%
“…18 For diseases requiring long-term drug administration such as those of the retina and vitreous body, a dexamethasone/cyclodextrin mixture applied to the ocular surface increased retinal penetration two-fold relative to systemic administration. 19 In situ gels are a novel type of ophthalmic drug delivery system with a longer retention time than that of existing approaches, and they reduce administration frequency and improve bioavailability. In vivo studies have shown that a temperature-sensitive chitosan hydrogel administered as ocular drops had high penetration and sustained release over 12 h while reducing intraocular pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Ocular steroids can be available in the systemic circulation and can cause systemic adverse effects. In a study, when the identical doses of steroid were administrated intravenously, intranasally and topically in the conjunctiva, the rates of systemic absorption have been found similar (7). Also, it has been previously reported that topical steroid eye drops may trigger the manifestation of HZ infection (8).…”
Section: Figure 1: the Typical Vesicular Rash Of Herpes Zoster Can Bementioning
confidence: 84%
“…Some studies have indicated that drugs may effectively reach the retina after topical administration. 10) It is important to investigate the detailed pharmacokinetics of the posterior eye tissues with respect to the concentration distribution of drugs.…”
Section: Regular Articlementioning
confidence: 99%